2014
DOI: 10.5380/ef.v0i9.29750
|View full text |Cite
|
Sign up to set email alerts
|

Perfil E Condição Bucal Do Paciente Portador De Doenças Infectocontagiosas Atendidos No Hospital Oswaldo Cruz - Curitiba/Pr

Abstract: RESUMOA saúde bucal afeta a qualidade de vida e dignidade pessoal dos pacientes. Esse impacto parece ser mais grave em indivíduos medicamente comprometidos ou hospitalizados. O projeto intitulado "Atenção estomatológica em pacientes hospitalizados e portadores de doenças infectocontagiosas" desenvolveu atividades de atenção primária à saúde por meio de ações educativas e preventivas das doenças bucais nos indivíduos portadores de doenças infectocontagiosas que estavam em tratamento no Hospital Oswaldo Cruz (Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 7 publications
0
8
0
2
Order By: Relevance
“…As much as 17 (60.7%) [3][4][5][6][7]10,18,19,[21][22][23][26][27]29,33 studies were published between 2014 and 2017, 4 (14.3%) 2,16,30,32 in 2011, 3 (10.7%) 24,25,28 in 2010, 2 (7.1%) 17,20 in 2013, and 1 (3.6%) in 2008 and 1 in 2012. 15,31 Most of the studies were conducted in São Paulo state, with 7 (25%) 2,15,17,19,22,24,26 publications, followed by the states of Santa Catarina (n=4, 14.3%), 7,25,28,32 Paraná (n=3, 10.7%) 6,13,30 and Mato Grosso (n=2, 5.6%). 18,23 The states of Bahia, Goiás, Mato Grosso do Sul, Minas Gerais, Pará, Paraíba, Pernambuco, Piauí, Rio Grande do Norte and Rio Grande do Sul had 1 (2.8%) publication each, accounting to 28% of the sample.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As much as 17 (60.7%) [3][4][5][6][7]10,18,19,[21][22][23][26][27]29,33 studies were published between 2014 and 2017, 4 (14.3%) 2,16,30,32 in 2011, 3 (10.7%) 24,25,28 in 2010, 2 (7.1%) 17,20 in 2013, and 1 (3.6%) in 2008 and 1 in 2012. 15,31 Most of the studies were conducted in São Paulo state, with 7 (25%) 2,15,17,19,22,24,26 publications, followed by the states of Santa Catarina (n=4, 14.3%), 7,25,28,32 Paraná (n=3, 10.7%) 6,13,30 and Mato Grosso (n=2, 5.6%). 18,23 The states of Bahia, Goiás, Mato Grosso do Sul, Minas Gerais, Pará, Paraíba, Pernambuco, Piauí, Rio Grande do Norte and Rio Grande do Sul had 1 (2.8%) publication each, accounting to 28% of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…In order to identify the scenario of hospital dentistry in Brazil through published studies, it was found that 6 (21.4%) [13][14][15]17,23,26 studies had a control group; 17 (60.7%) [4][5][6]16,18,19,[20][21][22]24,[27][28][29][30][31][32][33] were related to patients' oral health profile and 5 (17.9%) 2,3,7,10,25 were questionnaire-based studies of which 4 3,7,10 involved only patients and 1 25 involved patients, caregivers and healthcare professionals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations